57 Update of IMPACT Invasive Meningococcal Surveillance, 2016-2020. (21st October 2022) - Bettinger, Julie; Sadarangani, Manish; Le Saux, Nicole; Morris, Shaun; Top, Karina; Halperin, Scott; Tsang, Raymond
Abstract: Background: Meningococcal conjugate vaccine (MCV) programs in Canada began in 2002. Objectives: This study examines the most recent surveillance data to describe the current Canadian epidemiology of invasive meningococcal disease (IMD) and the effect of MCV programs, especially on age and serogroup distribution. Design/Methods: Active metropolitan area surveillance for hospitalization of adults and children due to IMD, which was defined as a clinical infection with Neisseria meningitidis isolated or detected by molecular methods or culture from a sterile body site. The study was conducted via the 12 centres of the Canadian Immunization Monitoring Program, Active (IMPACT) network from January 1, 2016 – December 31, 2020. Results: During 2016-2020, a total of 105 pediatric (<20 years of age) and 145 adult IMD cases occurred. Serogroup B accounted for the greatest proportion of pediatric cases (N=58, 55.2%), followed by W (n=19, 18.1%) and Y (n=9, 8.6%) and C (n=2, 1.9%). Among adults, serogroup W accounted for the majority of cases (n=55, 38.0%), followed by Y (n=41, 28.3%), B (n=33, 22.8%) and C (n=7, 4.8%). The age distribution for serogroups covered by MCV programs has shifted to adults. The median age was 24.2 years (33.4 mean). Whereas the median age of serogroup B cases was 7.7 years (19.4 years mean) with 63.7% of cases occurring in children < 19 years of age and 46.2% in children 0-4 years of age. A total of 20 people died from meningococcal infections in 2016–2020. Five deaths were in children, four from serogroup B and one from serogroup W. Fifteen deaths were in adults, one from serogroup B, eight from serogroup W, three from serogroup Y, and three from Non-typeable/Other/Unknown serogroups. Conclusion: Serogroup B, which is not covered by MCV programs, still accounts for the majority of pediatric IMD. Serogroup C has been controlled and rarely causes pediatric infection. With the implementation of MCV programs in children and adolescents, the median and mean age at infection has increased across all serogroups, except serogroup B. Serogroup W is still causing IMD among pediatric age groups.